Differences in fall-related characteristics across cognitive disorders - Minta, Karolina; Colombo, Giorgio; Taylor, William R.; Schinazi, Victor R. (Frontiers in Aging Neuroscience, 2023)
Approximately 40-60% of falls in the elderly lead to injuries, resulting in disability and loss of independence. Despite the higher prevalence of falls and morbidity rates in cognitively impaired individuals, most fall risk assessments fail to account for mental status. In addition, successful fall prevention programmes in cognitively normal adults have generally failed in patients with cognitive impairment. Identifying the role of pathological aging on fall characteristics can improve the sensitivity and specificity of fall prevention approaches. This literature review provides a thorough investigation into fall prevalence and fall risk factors, the accuracy of fall risk assessments, and efficacy of fall prevention strategies in individuals with diverse cognitive profiles. We show that fall-related characteristics differ between cognitive disorders and fall risk assessment tools as well as fall prevention strategies should critically consider each patient’s cognitive status to facilitate the identification of fallers at an earlier stage and support clinical decision-making.